International initiative for a curated SDHB variant database improving the diagnosis of hereditary paraganglioma and pheochromocytoma. Issue 8 (27th August 2021) - Ben Aim, Laurene; Maher, Eamonn R; Cascon, Alberto; Barlier, Anne; Giraud, Sophie; Ercolino, Tonino; Pigny, Pascal; Clifton-Bligh, Roderick J; Mirebeau-Prunier, Delphine; Mohamed, Amira; Favier, Judith; Gimenez-Roqueplo, Anne-Paule; et al.
Abstract : Background: SDHB is one of the major genes predisposing to paraganglioma/pheochromocytoma (PPGL). Identifying pathogenic SDHB variants in patients with PPGL is essential to the management of patients and relatives due to the increased risk of recurrences, metastases and the emergence of non-PPGL tumours. In this context, the 'NGS and PPGL (NGSnPPGL) Study Group' initiated an international effort to collect, annotate and classify SDHB variants and to provide an accurate, expert-curated and freely available SDHB variant database. Methods: A total of 223 distinct SDHB variants from 737 patients were collected worldwide. Using multiple criteria, each variant was first classified according to a 5-tier grouping based on American College of Medical Genetics and NGSnPPGL standardised recommendations and was then manually reviewed by a panel of experts in the field. Results: This multistep process resulted in 23 benign/likely benign, 149 pathogenic/likely pathogenic variants and 51 variants of unknown significance (VUS). Expert curation reduced by half the number of variants initially classified as VUS. Variant classifications are publicly accessible via the Leiden Open Variation Database system (https://databases.lovd.nl/shared/genes/SDHB ). Conclusion: This international initiative by a panel of experts allowed us to establish a consensus classification for 223 SDHB variants that should be used as a routine tool by geneticists in charge of PPGL laboratory diagnosis. This accurate classification of SDHB genetic variants will help to clarify the diagnosis of hereditary PPGL and to improve the clinical care of patients and relatives with PPGL.